Pengelolaan Kelompok Kerja Guru dalam Meningkatkan Profesionalitas Guru - Junjun Ade Permana; Alan Rusyadi; Awang Kustiawan; Lilis Kholisoh; Maman Herman (Journal of Education and Teaching (JET), 2022)
The purpose of this study was to explore the management of the Teacher Working Group (KKG in Bahasa). It is important because through the KKG, teachers will gain teaching readiness, and the professional abilities of teachers and the quality of their performance. The research method used is descriptive method with a qualitative approach. Data collection techniques in the form of interviews, observations, and documentation studies with informants consisting of school supervisors, principals, teachers, and the head of the KKG. The results showed that: the management of KKG in Cluster 3, Manonjaya District, Tasikmalaya Regency was optimal. Meanwhile, the professionalism of teachers is also increased.